2012
DOI: 10.1593/neo.121258
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Suppression of DNA Double-strand Break Repair

Abstract: c-Myc is a transcriptional factor that functions as a central regulator of cell growth, proliferation, and apoptosis. Overexpression of c-Myc also enhances DNA double-strand breaks (DSBs), genetic instability, and tumorigenesis. However, the mechanism(s) involved remains elusive. Here, we discovered that γ-ray ionizing radiation-induced DSBs promote c-Myc to form foci and to co-localize with γ-H2AX. Conditional expression of c-Myc in HO15.19 c-Myc null cells using the Tet-Off/Tet-On inducible system results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 55 publications
2
48
0
Order By: Relevance
“…In mammalian cells, overexpression of c-Myc increases the number of DNA double strand breaks (DSBs), as assayed by the level of γ-H2A.X, a phospho-histone marker of DSBs [9], [11][13], [15]. To determine if this is a conserved feature of Myc family proteins, we overexpressed Drosophila Myc in the dorsal compartment of the larval wing imaginal disc using apterous-Gal4 (ap-Gal4) and showed that this led to a ∼2-fold increase in the number of γ-H2A.X positive cells (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells, overexpression of c-Myc increases the number of DNA double strand breaks (DSBs), as assayed by the level of γ-H2A.X, a phospho-histone marker of DSBs [9], [11][13], [15]. To determine if this is a conserved feature of Myc family proteins, we overexpressed Drosophila Myc in the dorsal compartment of the larval wing imaginal disc using apterous-Gal4 (ap-Gal4) and showed that this led to a ∼2-fold increase in the number of γ-H2A.X positive cells (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of Myc family proteins increases genomic instability [6], [9], [12], [24][26], [47]. While understanding the effects of overexpressed Myc has clear relevance for understanding diseases caused by dysregulation of Myc such as cancer, we also wish to test a role for endogenous Myc in influencing mutation load.…”
Section: Resultsmentioning
confidence: 99%
“…3,11 Ku70 is a protein that binds to DNA double-strand break (DSB) ends and is required for the non-homologous endjoining pathway of DSB repair. [12][13][14][15] The Ku70 protein consists of three structural domains, including the N-terminal, central (that is, DNA binding) and C-terminal domains. 16,17 Ku70 usually heterodimerizes with Ku86, which forms a functional complex for DSB repair.…”
mentioning
confidence: 99%
“…In addition to DNA-PKcs and c-Mycmediated functional regulation [31,32], it is interesting to answer whether DNA-PK can act as a platform when interacting with c-Myc to mediate its direct involvement on DNA damage response. After a DSB, histone H2AX is phosphorylated at Ser139 to form c-H2AX foci enriched at DSB sites to function as a molecular machine of DNA damage signalling and response [33].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies regarding the involvement of c-Myc in regulating cellular sensitivity to ionizing radiation, major attentions have been paid to c-Myc-mediated regulation of apoptosis or of repair genes expression or to the regulation of autophagy or the ageing process [26,31,32,37]. In recent years, studies on the various checkpoints in the c-Myc-mediated regulation of energy metabolism or carcinogenesis have provided new hypotheses regarding the consideration of c-Myc as a molecular target in cancer therapy [38,39].…”
Section: Discussionmentioning
confidence: 99%